Assessment of morpho-molecular inter-nodular heterogeneity in the primary and metastatic disease of patients with hepatocellular carcinoma - Martins Filho, Sebastião Nunes (2019)
INTRODUCTION: Hepatocellular carcinoma (HCC) is a deadly cancer with increasing incidence in western countries. Diagnosis of HCC is based on imaging exams and most Cancer Centers do not recommend core-biopsies for definitive histopathological confirmation. Moreover, only patients with early disease stage are eligible to curative-intent treatments including surgical resection and liver transplantation. Hence, access to tissue samples in HCC patients with intermediate and advanced disease is limited, which further precluded the evaluation of morphological features and molecular drivers of HCC dissemination, particularly in relation to metastatic spread. Evaluation of autopsy specimens with adequate representation of primary and metastatic disease can overcome such limitations and provide insights on the mechanisms and patterns of distant dissemination in HCC. METHODS: This study included 88 autopsy specimens from patients with HCC, including 20 with distant metastases. Tissue microarrays (TMA) were generated from 194 hepatic and 36 extra-hepatic nodules histologically available from these patients. All nodules were assessed for multiple histological features including degree of differentiation, nuclear, nucleolar and architectural grades, and cellular crowding. Immunohistochemistry (IHC) was performed for markers of hepatocyte differentiation (HepPar1, Arginase and CD10), CTNNB1 mutation status (beta-catenin and Glutamine Synthetase), HCC stem-like features (Keratin 19, CD44 and EpCam), and epithelial-mesenchyme transition (Vimentin and Claudin 1). Phenotypic heterogeneity in the primary disease was assessed in 50 patients with multiple hepatic nodules and heterogeneity in the metastatic disease was evaluated in 12 patients with multiple extra-hepatic nodules. Mutations in the TERT-promoter region was evaluated in six patients with multi-nodular primary and metastatic disease. RESULTS: Metastatic sites included lungs (16/20, 80%), peritoneum (4/20, 20%) lymph nodes (4/20, 20%) and adrenal gland (3/20, 15%). Subclinical micro-metastases, undetected in imaging and macroscopic examination, were identified in 30% of the patients with disseminated disease to the lung. AFP serum concentration >= 100 ng/mL, dominant nodule >= 5.0 cm, multi-nodularity, macrovascular invasion, high histological, nuclear and architectural grades, cellular-crowding, and expression of Keratin 19 and EpCam in the primary disease were associated with the presence of distant metastases in HCC. Histological and IHC analyses showed that all HCC metastatic nodules could be traced back to the primary disease. Phenotypic inter-nodular heterogeneity was detected in 27/50 (54%) patients with multinodular hepatic disease. Heterogeneity was less pronounced in extra-hepatic nodules, being present in only 2/12 (17%) patients with multiple metastatic tumors. These results were further validated by the limited mutation heterogeneity of the TERT-promoter region in metastatic compared to primary nodules. CONCLUSIONS: HCC shows a strong hematogenous tropism and predilection for lung dissemination. Metastatic HCC nodules are enriched in histological features of aggressive behavior and in markers of stem-like properties. The limited phenotypic internodular heterogeneity within the primary compared to metastatic nodules suggests evolutionary constrains in HCC extra-hepatic dissemination